2013
DOI: 10.4028/www.scientific.net/msf.765.761
|View full text |Cite
|
Sign up to set email alerts
|

High Strength Aluminium Sheet Metal Joining by Resistance Spot Welding

Abstract: Aluminium AA7075 is well known as extrusions, plate or sheet metal predominately in aerospace applications. The continuing efforts for reducing the weight but still maintaining the safety of vehicle structures are opening up the way for this alloy in automotive applications. Since this branch is very different to space as well as aircraft industries in manufacturing methods, costs and production numbers, the development of appropriate processes is necessary. After showing a high potential for deep drawing of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Additional investigations showed that remaining dry lubricants do not decrease the static mechanical properties or increase the number or size of pores [6]. Continuing analysis will focus on dynamic testing, the influence of coil/sheet coatings on the process as well as on corrosion performance and mechanical behaviour, respectively.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Additional investigations showed that remaining dry lubricants do not decrease the static mechanical properties or increase the number or size of pores [6]. Continuing analysis will focus on dynamic testing, the influence of coil/sheet coatings on the process as well as on corrosion performance and mechanical behaviour, respectively.…”
Section: Discussion Of Resultsmentioning
confidence: 99%